PEMAHAMAN RELASIONAL SISWA SMP DALAM MENYELESAIKAN MASALAH BERDASARKAN GAYA BELAJAR VISUAL: Relational Understanding of Junior High School Students in Solving Problems Based on Visual Learning Styles - Ishariyadi, Ishariyadi (Aksioma, 2025)
Learning styles based on sensory modalities are divided into three categories: visual, auditory, and kinesthetic. This research aims to describe the relational understanding profile of junior high school students with a visual learning style in solving set operation problems. A qualitative descriptive approach was used to conduct this research. The research began by administering a learning style questionnaire to students, as well as observing students' abilities from the daily grade records held by the teacher. After identifying one student, a task sheet was given to be completed and an interview was conducted. In the implementation of Polya's stages, students with a visual learning style emphasized the sense of sight, namely by repeatedly observing information, speaking hastily, and focusing more on the given problem. The research results indicate that the relational understanding of students with a visual learning style involves paying attention to the given task multiple times. In creating a plan, students with a visual learning style convey it with poorly structured language and appear rushed. In carrying out the plan, students with a visual learning style tend to focus on the problem first. In reviewing, students with a visual learning style repeatedly observe the problem and their answer sheet.